Dearomatization reaction of β-naphthols with disulfurating reagents. Issue 40 (28th September 2021) - Zhang, Shan-Shan; Xue, Jiahui; Gu, Qing; Jiang, Xuefeng; You, Shu-Li
Abstract : TsOH-catalyzed intermolecular dearomatization reactions of β-naphthols with electrophilic disulfurating reagents were developed, affording β-naphthalenones in up to 94% yield. Abstract : p -TsOH-catalyzed intermolecular dearomatization reactions of β-naphthols with disulfurating reagents were developed. Various β-naphthalenones bearing a quaternary carbon stereogenic center were obtained smoothly in good to excellent yields with high chemoselectivity in the presence of 5 mol% p -TsOH. This reaction features mild reaction conditions and excellent functional group tolerance.